Stratigraphy and paleomagnetism of a 3-km-thick Miocene lava pile in the Mjoifjrdur area, eastern Iceland (Dataset) ... - Kristjansson, Leo; Agust Gudmundsson; Haraldsson, Hreinn (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Stratigraphy and paleomagnetism of a 3-km-thick Miocene lava pile in the Mjoifjrdur area, eastern Iceland ...